2019
DOI: 10.1248/cpb.c19-00171
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Assembly of Amyloid β-Peptides in the Hydrophobic Environment

Abstract: Fibrillated aggregation of amyloid β (Aβ) peptides is a potential factor causing toxic amyloid deposition in neurodegenerative diseases. A toxic fibril formation of Aβ is known to be enhanced on the ganglioside-rich lipid membrane containing some amounts of cholesterol and sphingomyelin. This ganglioside-rich membrane is supposed to provide a hydrophobic environment that promotes the formation of Aβ fibrils. Molecular dynamics simulations were carried out to investigate the structure of Aβ complex in the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…AFM visualization and MD simulations demonstrated that cholesterol in the lipid bilayer significantly increased Aβ42 surface aggregation, but not membrane penetration, at monomer concentrations as low as nM. These results suggest the importance of membrane lipids for the local concentration, clustering, and conformation change of Aβ into a β-structure-rich form of amyloid peptides (Drolle et al, 2012 ; Qu et al, 2019 ; Banerjee et al, 2021 ). It is speculated that the AD-associated elevation of cholesterol levels in the PM may increase the likelihood of membrane-dependent Aβ42 aggregation (Banerjee et al, 2021 ).…”
Section: Amyloid β Toxicity Related To Membrane Cholesterolmentioning
confidence: 94%
See 2 more Smart Citations
“…AFM visualization and MD simulations demonstrated that cholesterol in the lipid bilayer significantly increased Aβ42 surface aggregation, but not membrane penetration, at monomer concentrations as low as nM. These results suggest the importance of membrane lipids for the local concentration, clustering, and conformation change of Aβ into a β-structure-rich form of amyloid peptides (Drolle et al, 2012 ; Qu et al, 2019 ; Banerjee et al, 2021 ). It is speculated that the AD-associated elevation of cholesterol levels in the PM may increase the likelihood of membrane-dependent Aβ42 aggregation (Banerjee et al, 2021 ).…”
Section: Amyloid β Toxicity Related To Membrane Cholesterolmentioning
confidence: 94%
“…After interaction with a membrane, Aβ can damage the bilayer through a “carpeting effect” in which the amyloid disrupts membrane integrity by covering its surface, it can exert detergent-like effects, or amyloid peptides can self-organize into transmembrane ion channels (Figure 1 ; Williams and Serpell, 2011 ; Cecchi and Stefani, 2013 ; Press-Sandler and Miller, 2018 ; Sciacca et al, 2018 ). Due to the presence of different nucleation centers, the nature of the lipid membrane determines the state of the peptide, which is closely linked to the processes of Aβ assembly and toxicity (Ding et al, 2012 ; Cecchi and Stefani, 2013 ; Pannuzzo, 2016 ; Bera et al, 2019 ; Qu et al, 2019 ).…”
Section: Amyloid β Toxicity Related To Membrane Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…23) MM calculation is useful for analyzing intermolecular interactions such as antibody recognition of antigens 24,25) and the amyloid peptide addiction to a membrane surface. 26) MM calculation is also useful for analysis of compound-protein interactions 27) and is utilized for the molecular design of candidate inhibitors. 28) The compounds selected by the computer screening were examined in experiments for their potency to block the enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%